E-HRM: PAIN OR GAIN FOR HRM EFFECTIVENESS - Felix Pratamajaya Kwan; Leonardus Riko Hermawan; Nadhilah Hafizhi (Jurnal TAM (Technology Acceptance Model), 2019)
Nowadays, technology has a huge impact on helping human working activities. E-HRM practices such as e-recruiting, e-learning, workforce planning, e-income tax, e-salary, mobile absent, etc, can be seen as activities that help the organization to meet their objectives. This study will explain factors HRM effectiveness through UTAUT analysis of E-HRM in the organization. Using a quantitative method, we collect data with a questionnaire at eight companies in Indonesia, Structural Equations Modelling (SEM) being used in this research. We assume that E-HRM will help the organization by increasing its effectiveness.